Financial stability and public confidence in banks - Lucy Chernykh; Denis Davydov; Jukka Sihvonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
We use a novel, household opinions-based measure – Public Confidence in a Bank – to explore the role of bank-level and system-wide determinants of customers' trust in banks. Our study covers a panel of approximately 260 large Russian commercial banks publicly monitored during 2010–2017. We find that public confidence in a bank is highly sensitive to the industry-level financial stability indicators, but less sensitive to bank-level risk characteristics. This result reveals an important role of overall banking sector stability in determining public perception of the safety and soundness of individual banks.
URN:NBN:fi:bof-201902211070
Keywords: G21; D14; 330; financial stability; public confidence; bank failures; customer opinions; online reviews